STRATEGI PENGEMBANGAN OLAHAN PRODUK BERBAHAN DASAR JAGUNG PULUTDALAM MENINGKATKAN EKONOMI MASYARAKAT DI DESA MULYONEGORO - Halid, Amir; Moonti, Agustinus; Madjid, Tarisa; Nai, Gufrana Mukhlisa; Yusup, Nurhayati; Syukur, Rafiq Ramdan; Bayhaqi, Yody (Universitas Negeri Gorontalo, 2023)
Mulyonegoro Village is one of the corn-producing villages located in Pulubala District, the corn produced is hybrid corn, pulut corn and sweet corn. Based on these problems, there is a need for creativity and innovation in the utilization of corn in Mulyonegoro Village. In Mulyonegoro Village, farmers and MSME actors were chosen as the targets for this activity because given the large opportunities to improve skills in processing corn into a product that can add to the economy of the people in Mulyonegoro Village. The availability of raw materials, time and place is seen as a big capital, so that through this activity other needs in the form of production tools and marketing media as a complement will be provided by MBKM KKN Students. The purpose of this activity is to increase people's income by providing innovation in the utilization of corn into a contemporary product. Counseling and training took place at the Mulyonegoro Village Office, the target of this activity was BUMDES and communities that have MSMEs in Mulyonegoro Village. The method used is Community Development, namely conducting counseling and mentoring in the manufacture of processed pulut corn products. The result of this activity is to increase the income of the people of Mulyonegoro Village and to introduce corn products as an agricultural product that can be processed into various types of food that are ready to be marketed.